Pharmacokinetics and tolerability of a new formulation of omeprazole in the horse. Issue 4 (24th November 2016) - Di Salvo, A.; Busechian, S.; Zappulla, F.; Marchesi, M. C.; Pieramati, C.; Orvieto, S.; Boveri, M.; Predieri, P. G.; Rueca, F.; della Rocca, G.
Abstract : A new formulation of omeprazole in gastro‐resistant granules was tested with regard to its pharmacokinetics and tolerability. Twenty‐four horses were randomly divided into three groups (8 horses/group) and treated, according a parallel study design, as follows: Group A untreated (control group), Group B received 4 mg/kg of omeprazole, and Group C received 12 mg/kg of omeprazole, both of which were treated orally once a day for 90 days. Blood samples, taken from Group B subjects during the 1st and the 29th day of treatment at pre‐established time points, were used to determine the concentration–time curves of omeprazole. The treatments were found to be safe and well tolerated by the horses. The serum hematological and biochemical values were within reference ranges for the entire observational time. No accumulation of the drug was found after 29 days of treatment. Lower C max and AUCs were obtained at the 29th day of treatment.